THU0667 A qualitative and quantitative comparison of synovial biopsy techniques during clinical trials of inflammatory arthritis. (15th June 2017) - Humby, F; Bugatti, S; Filer, A; Kelly, S; Manzo, A; Souza, E; Romao, V; Rocher, V; Hands, R; Wechalekar, M; Fonseca, J; Montecucco, C; et al.
Abstract : Background: Synovial tissue is an attractive area of research for biomarkers of disease outcome in RA. Currently acquisition of synovial tissue using an arthroscopic approach in clinical trials is recommended though two US-guided techniques have been described, a portal and forceps (P&F) approach and an adaptation using a quick core needle (NB). However before US-guided biopsy techniques are widely adopted into clinical trials validation of performance against arthroscopy is required. Objectives: To evaluate whether there were significant differences in synovial sampling quality and quantity between arthroscopic, US-P&F and US-NB procedures within the context of clinical trials. Methods: This was a multicentre retrospective analysis of inflammatory arthritis patients recruited to clinical trials utilizing US-guided NB (Barts Health NHS Trust), US-guided P&F (ICRSS Policlinico San Matteo and University Hospital Birmingham) and arthroscopic biopsy (Repatriation General Hospital). Paraffin embedded synovial sections from each procedure underwent H&E staining and sections examined for intact cell lining layer (graded sections). Biopsy procedures were segregated into large (knee) and small joint procedures (wrist/MCP) for analysis. Proportion of samples yielding graded tissue per procedure was recorded. Using CellSens Dimensions software the mean area of synovial tissue obtained per procedure was determined. In addition the degree of synovitis was assessed using semi-quantitiative scoring (0–9). Results: 78 patient procedures were evaluated, 22 on small joints (11 US-NB, 11 US P&F) and 56 on large joints (11 US-NB, 35 US-P&F, 10 arthroscopic). 47 patients had RA, 11 undifferentiated arthritis and 10 psoriatic arthritis. Arthroscopic sampling resulted in a significantly higher area of tissue retrieved per procedure than US P&F or US-NB. There were no significant differences in proportion of graded samples per procedure suggesting quality of synovial tissue was preserved between techniques. Finally no significant differences in degree of histological synovitis were demonstrated between sampling techniques. Conclusions: The results suggest that US-guided biopsy provides a reliable method for sampling synovial tissue of comparable quality to that obtained from arthroscopy. However when sampling large joints arthroscopic techniques, and when sampling small joints US-P&F yield a significantly higher quantity, though not quality, of tissue per procedure than US-NB. These results may influence choice of biopsy technique when designing clinical trial protocols in inflammatory arthritis. Disclosure of Interest: None declared